Complex clinical and cytological diagnosis of eye adnexa epithelial tumors - S. V. Saakyan; M. G. Zhiltsova; Yu. I. Borodin; A. Yu. Tsygankov (Российский офтальмологический журнал)
Purpose. Studying clinical and cytological signs of malignant epithelial genesis tumors of eye adnexa. Material and methods. In 2015–2020, 308 patients aged from 23 to 87 (58.0 ± 6.7) years with suspected malignant neoplasms of eyelid skin and conjunctiva were cytologically examined. The material for cytological examination was obtained by scraping (n = 271; 88 %), imprinting (n = 27; 8.8 %), and fine needle aspiration biopsy (n = 10; 3.2 %) if the neoplasm was more than 10 mm thick. Preparations were processed and fixed according to the standard technique using panchromic Pappenheim staining. Results. The cytological analysis confirmed the clinical diagnosis and the epithelial genesis of the malignant neoplasm in 273 (88.7 %) patients. The benign nature of the tumor was confirmed in 17 patients (5.5 %) and the non-tumor nature of the process was confirmed in 11 patients (3.6 %). In the group of malignant tumors, basal cell cancer prevailed, affecting 240 patients (87.9 % of all malignant tumors). 27 patients (9.9% ) had squamous cell cancer, 4 patients had meibomian gland cancer in 4 patients, and 2 patients had undifferentiated cancer. Benign tumors included papillomas (n = 11), while tumor-like lesions included atheromas (n = 3) and granulation polyps (n = 3). Non-tumor lesions involved productive inflammation of the chalazion type (n = 7), or chronic inflammation of a reactive nature (n = 4). 22 patients had histological examination to check the diagnosis, in all cases the histological outcome coincided with the cytological diagnosis. Conclusion. The comprehensive clinical and cytological study allowed us to specify cytomorphological characteristics of epithelial tumors of the eye adnexa: the basal cell cancer and its varieties according to the clinical forms of the tumor, squamous cell cancer and meibomian gland cancer, and papilloma. The complex clinical and cytological method of diagnostics is easily applicable in out-patient conditions, allowing us to specify the diagnosis during the initial visit, which considerably reduces the time required for full patient’s examination.